Real Interest Rates, Home Goods, and Optimal External Borrowing - Dornbusch, Rudiger (Journal of Political Economy, 1983)
The paper investigates the optimal time path of consumption and external borrowing in the dependent economy model. The small country faces given world prices and a given world real interest rate. The presence of a home goods sector implies that the relevant real interest rate appropriate to consumption decisions depends on the rate of change of the real price of home goods. The paper shows how transitory disturbances in output or in the world real interest rate affect the time profile of consumption and the trade balance. In particular it is shown that the presence of a home goods sector dampens the consumption effects of changes in the world interest rate.